Big Data Applications in Online Psychological Counseling: A Systematic Literature Review - Tissa Maharani (Asosiasi Dosen Muda Indonesia, 2026)
The development of digital technology has transformed mental health services, including online psychological counseling. The increasing use of digital platforms generates large volumes of psychological and behavioral data that can be analyzed through Big Data approaches to support assessment, intervention, monitoring, and decision-making processes. This study aims to systematically review the application of Big Data in online psychological counseling by examining its implementation approaches, supporting technologies, benefits, challenges, and future research directions. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Literature searches were performed in Scopus, ScienceDirect, PubMed, SpringerLink, and Google Scholar, resulting in 20 eligible studies published between 2016 and 2026 for qualitative synthesis. The findings indicate that Big Data has been applied in data integration, behavioral analysis, counseling conversation analysis, clinical decision support, and digital intervention development. Key enabling technologies include Natural Language Processing, Machine Learning, social media analytics, conversational agents, and Large Language Models. The reviewed studies highlight several benefits, including personalized mental health services, early identification of mental health risks, improved accessibility, and enhanced scalability of counseling support. However, important challenges remain, particularly regarding data privacy, informed consent, algorithmic bias, transparency, fairness, and the generalizability of computational models. Future research should focus on integrating heterogeneous data sources, developing explainable artificial intelligence systems, strengthening ethical governance frameworks, and evaluating long-term effectiveness in real-world counseling settings. Overall, Big Data demonstrates considerable potential to support more effective, ethical, and evidence-based digital mental health services.